2007
DOI: 10.1111/j.1528-1167.2007.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

ABC Transporters during Epilepsy and Mechanisms Underlying Multidrug Resistance in Refractory Epilepsy

Abstract: Summary:It is estimated 20-25% of the epileptic patients fails to achieve good control with the different antiepileptic drugs (AEDs) treatments, developing refractory epilepsy (RE). Discovered first in cancer, the activity of P-glycoprotein (P-gp) and others ABC transporters as multidrug-resistance-associated proteins (MRPs) and breast cancer resistant protein (BCRP) are directly related with the refractoriness. We have observed the overexpression of these all transporters in the brain of patients with RE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(166 citation statements)
references
References 57 publications
2
150
0
7
Order By: Relevance
“…This phenomenon is thought to be caused by overexpression of drug efflux transporter genes, such as MDR1 at the blood-brain barrier, that limit AED access to the brain. 16,17 The target hypothesis, on the other hand, contends that target receptor sites are somehow altered in the epileptic brain so that they are much less sensitive to the anticonvulsant effects of systemically administered drugs. So far, a reduction in drug target sensitivity in chronic human and experimental epilepsy has been suggested for the voltage-gated sodium channel and the GABA-A receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is thought to be caused by overexpression of drug efflux transporter genes, such as MDR1 at the blood-brain barrier, that limit AED access to the brain. 16,17 The target hypothesis, on the other hand, contends that target receptor sites are somehow altered in the epileptic brain so that they are much less sensitive to the anticonvulsant effects of systemically administered drugs. So far, a reduction in drug target sensitivity in chronic human and experimental epilepsy has been suggested for the voltage-gated sodium channel and the GABA-A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The candidate genes with a potential influence on AED response tested in this study were as follows: (1) genes encoding drug transporters, MDR1 (ABCB1), MRP2 (ABCC2) and BCRP (ABCG2), as overexpression of these genes has been observed in the brains of patients with refractory epilepsy 16,17 and (2) genes encoding drug targets such as voltage-gated neuronal sodium channels (SCN1A, SCN1B and SCN2A), potassium channels (KCNQ2, KCNQ3 and KCNQ5), calcium channels (CACNA1H), chloride channels (CLCN2), acetylcholine receptors (CHRNA4 and CHRNB2) and g-aminobutyric acid (GABA) receptors (GABRA1 and GABRG2), as they are the main therapeutic targets of AEDs and are known to be causative of familial epilepsy syndromes, 10,18,19 and (3) genes encoding neurotransmitter transporters (EAAT1, EAAT2, EAAT3, VGLUT1, VGLUT2, VGLUT3, GAT1 and GAT3), as they are the potential therapeutic targets of AEDs. 20 …”
Section: Candidate Genes For Aed Responsementioning
confidence: 99%
“…The "transporter`s hypothesis" to explain the refractoriness in epilepsy need not only a functional up-regulation of these transporters at BBB level to clean/export AEDs, but also they should be expressed on previously non-expressing cell as neurons. The inducible properties of these transporters as well as the the pharmacoresistant phenotype [9] links pharmacoresistance with epileptogenesis, as discussed below.…”
Section: Abc-transporters In the Brainmentioning
confidence: 99%
“…Interestingly, through the axis glutamate/NMDA receptor/cyclooxygenase-2 (COX-2) signaling, glutamate can induces overexpression of P-glycoprotein (P-gp) in brain [7,8]. The efflux of drugs by the multidrug transporters, particularly P-gp (ABCB1-transporter) is one of the principal means by which several patients with pharmacoresistant epilepsy develops refractoriness to a wide spectrum of antiepileptic drugs (AEDs) [9,10].…”
mentioning
confidence: 99%
“…It has been suggested that P-gp overexpression at the BBB lead to therapeutic failure of AEDs by several studies using rodent epilepsy models and human epileptic tissue [96, 97]. Adding a P-gp inhibitor to the anti-epileptic treatment regimens has been shown to reverse the drug-resistant phenotype [98]. The generations of inhibitors of P-gp, such as tariquidar, have been examined in preclinical and clinical studies; however, these trials have largely failed to demonstrate an improvement in therapeutic efficacy [99].…”
Section: Roles Of Immune and Inflammation In Drementioning
confidence: 99%